Computational discovery of DENV-3 RdRp allosteric inhibitors: biological evaluation and mechanistic studies - Gokul Krishnan Nagendran; Swati Fageria; Divya Bhatt; Neetu Malya; Akansha Belwal; Shruti Gautam; Muskan Singhal; Ayesha Fatima; Mamta Choudhary; Vineeta Rai; Chetan D. Meshram; Sathish Kumar Mudedla (Molecular Diversity, 2026)

Polar Winter Processes: An Under-Represented Research Focus within the Coupled Earth System - Xin Yang; Xiangdong Zhang; Ankit Agarwal; Rajendran Shobha Ajin; Thomas J. Bracegirdle; Peter Convey; Rainette Engbers; Markus M. Frey; Eugenia M. Garbarini; Irina Gorodetskaya; Xianda Gong; Sergi González-Herrero; et al. (Advances in Atmospheric Sciences, 2026)
Observing winter processes during the extended cold season is crucial not only for understanding polar and global coupled Earth system but also for enhancing capability of year-round prediction, especially in the context of Arctic amplification and the drastic decrease in sea ice extent and thickness at both poles. However, harsh environmental conditions and logistical challenges have left polar winter Earth system processes substantially under-observed compared with those during summer. This disparity creates major obstacles for studying these processes and their roles in shaping the state and variability of the Earth systems, as well as for accurately simulating them in Earth System Models (ESMs). Consequently, these limitations introduce considerable uncertainties in ESMs regarding the understanding, prediction, and projection of Earth system variability and changes. This study discusses key polar winter processes and evaluates critical knowledge gaps. It identifies three urgent research priorities for the near future: (i) sources, properties, and transport of polar winter aerosols and their interactions with clouds; (ii) polar storms and their interactions with the underlying sea ice and ocean; and (iii) persistent discrepancies in understanding and predicting large-scale teleconnections between polar regions and lower latitudes. To address these priorities, this perspective recommends strengthening coordinated, winter-focused, international and multidisciplinary observational efforts, for example, through initiatives such as the Fifth International Polar Year and the ongoing international Antarctica InSync programme. These initiatives would lay groundwork for designing future sustainable winter process observations.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Biophysical basis and morphological traits conferring resistance to yellow stem borer, Scirpophaga incertulas (walker) in land races of rice (Oryza sativa L.) - Divya D. Mallesh; Vijaykumar Lingaraj; B. Shivanna; Reddy C. N. Lakshminarayana; M. S. Kitturmath; H. R. Raveendra; K. R. Ashoka (International Journal of Tropical Insect Science, 2026)

Stress Resilience in Tuber Crops: A Closer View on Genome Editing and Molecular Approaches - Pandian Rajendran; Krishnagowdu Saravanan; B. Jagadhesan; R. Ramesh; Divya Bharathi; Pavithra Suryakumar; Nitin Sharma; Yogesh Yele; Ashish Marate; Niranjan Prasad; N. D. Vinay; Palaiyur Nanjappan Sivalingam; et al. (Journal of Plant Growth Regulation, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Unraveling allelic variations and population structure in wild species and cultivars of rice (Oryza spp.) for yield-related genes - Musku Sridhar; Divya Balakrishnan; M. S. Anantha; P. Senguttuvel; R. M. Sundaram; L. V. Subbarao; D. Aleena; Ch. Raveendra; S. Rathod; S. R. Chimmli; G. Padmavathi; M. Sujatha; et al. (Cereal Research Communications, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

Genetic diversity studies in bell pepper (Capsicum annuum L. var. Grossum Sendt.) genotypes for growth, yield and quality traits - Divya Arti; D. K. Mehta; Shraddha Shraddha; Jyoti Singh; Nirankar Nirankar (Vegetos, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Deciphering mating type and population genetic landscape of Magnaporthe population adapted to millets and rice in blast hotspots of India - K. B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H. D. Vinaykumar; Divya Bhandhari; H. R. Raveendra; T. S. S. K. Patro; T. V. Krishna; T. E. Nagaraja; R. Madhusudhana; C. Tara Satyavathi (Archives of Microbiology, 2025)

Optimized biodiesel production from Java olive seeds using a novel magnetic nanobiocatalyst and advanced optimization techniques - L.R. Monisha Miriam; Ajith J. Kings; Jain B. Marshel; R. Edwin Raj; S. Indran; D. Divya (Biomass and Bioenergy, 2025)

Quercus leucotrichophora strategies to adapt the different environments in Western Himalaya - Pooja Negi; Deep C. Tiwari; Monika Rawat; Shinny Thakur; Divya Khatri; Rajiv Pandey; I. D. Bhatt; Sunil Nautiyal (Plant Ecology, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

High-dimensional mediation analysis to elucidate the role of metabolites in the association between PFAS exposure and reduced SARS-CoV-2 IgG in pregnancy - Haibin Guan; Jia Chen; Kirtan Kaur; Bushra Amreen; Corina Lesseur; Georgia Dolios; Syam S. Andra; Srinivasan Narasimhan; Divya Pulivarthi; Vishal Midya; Lotje D. De Witte; Veerle Bergink; et al. (Science of The Total Environment, 2025)

Bayesian neural networks for probabilistic modeling of thermal dynamics in multiscale tissue engineering scaffolds - Janjhyam Venkata Naga Ramesh; Abhilash Sonker; G. Indumathi; D. Balakrishnan; Divya Nimma; Jayavarapu Karthik (Journal of Thermal Biology, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

Advancements in graphene and its derivatives based composite Materials: A comprehensive review on Synthesis, Characterization, and supercapacitive charge storage - Dhanaji Malavekar; Divya Pawar; Ajinkya Bagde; Sambhaji Khot; Suraj Sankapal; Shital Bachankar; Sharadchandra Patil; Chandrakant D. Lokhande; Jin Hyeok Kim (Chemical Engineering Journal, 2024)

Remote Sensing–Based UAV Imaging in Heat Pattern Analysis Impact on Climate Change Detection Using Fuzzy Stacked Lasso Elastic-Net Model - M. Sailaja; M. Prema Kumar; B. Swarna Jyothi; G. L. Narasamba Vanguri; S. Manjula; D. Divya Priya (Remote Sensing in Earth Systems Sciences, 2024)

Remote Sensing-Based Earth Climate Detection in Geoscience Model with Artificial Intelligence Application - Aarti Amod Agarkar; Mandar S. Karyakarte; Gajanan Chavhan; I. A. Ariffin; Milind Patil; Linginedi Ushasree; D. Divya Priya (Remote Sensing in Earth Systems Sciences, 2024)

Land use and altitudinal variability in biomass and carbon storage potential in mid-hill and sub-humid conditions of north-western Himalayas - Priyanka Rajput; D. R. Bhardwaj; Jatin Kumar; Saakshi; Prashant Sharma; Aalok Gulabrao Yewale; Divya Khatri (Environment, Development and Sustainability, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Genomic patterns of selection in morphometric traits across diverse Indian cattle breeds - Divya Rajawat; Sonali Sonejita Nayak; Karan Jain; Anurodh Sharma; Subhashree Parida; Sarada Prasanna Sahoo; Bharat Bhushan; D. B. Patil; Triveni Dutt; Manjit Panigrahi (Mammalian Genome, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

Pharmacology of Manilkara hexandra leaf extract: potent antimalarial by targeting β-hematin formation and pro-inflammatory cytokine investigation - Ravi Kumar; Saurabh Kumar; Parmanand Kumar; Divya Bhatt; Deepika Srivastava; Narendra Kumar; D. U Bawankule; Anirban Pal (Vegetos, 2024)

Stability analysis and genetic mapping for yield traits of rice wild introgression lines - N. P. S. De Silva; P. Magudeeswari; Divya Balakrishnan; V. Gouri Shankar; B. Kavitha; A. Krishnamraju; P. Prashanthi; K. Vaibhav; D. S. Chary; S. N. C. V. L. Pushpavalli; Sarla Neelamraju (Cereal Research Communications, 2024)

Protective effects of flaxseed oil against dexamethasone induced skeletal muscle atrophy on rats - Sneha Desai; Aayushi Balda; Divya D; Kamsagara Linganna Krishna (South African Journal of Botany, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Toxicity prediction and analysis of flavonoid apigenin as a histone deacetylase inhibitor: an in-silico approach - N. Divya Rajaselvi; M. D. Jida; Devu B. Nair; S. Sujith; Nisaath Beegum; A. R. Nisha (In Silico Pharmacology, 2023)

Evaluation of Thermostable Biomolecule Cocktail from Algal-associated Hot Water Spring Bacteria for Antibiofilm Activities - Mubassira K. Shaikh; Divya D. Patel; Shraddha C. Dobariya; Anoop R. Markande (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Reversibility controls on extreme methane clumped isotope signatures from anaerobic oxidation of methane - Jiarui Liu; Rachel L. Harris; Jeanine L. Ash; James G. Ferry; Sebastian J.E. Krause; Jabrane Labidi; Divya Prakash; Barbara Sherwood Lollar; Tina Treude; Oliver Warr; Edward D. Young (Geochimica et Cosmochimica Acta, 2023)

A propitious role of marine sourced polysaccharides: Drug delivery and biomedical applications - Ameya Sharma; Ishnoor Kaur; Divya Dheer; Manju Nagpal; Pradeep Kumar; D. Nagasamy Venkatesh; Vivek Puri; Inderbir Singh (Carbohydrate Polymers, 2023)

Cross-sectional associations of maternal PFAS exposure on SARS-CoV-2 IgG antibody levels during pregnancy - Kirtan Kaur; Corina Lesseur; Lixian Chen; Syam S. Andra; Srinivasan Narasimhan; Divya Pulivarthi; Vishal Midya; Yula Ma; Erona Ibroci; Frederieke Gigase; Molly Lieber; Whitney Lieb; et al. (Environmental Research, 2023)

Seasonal forecasting of tropical cyclones over the Bay of Bengal using a hybrid statistical/dynamical model - C. T. Sabeerali; O. P. Sreejith; Nachiketa Acharya; Divya E. Surendran; D. S. Pai (International Journal of Climatology, 2022)
The post‐monsoon (October–November–December) tropical cyclone (TC) over the Bay of Bengal is one of the most devastating natural disasters causing economic and human losses over India and its neighbouring countries. This study discusses a hybrid statistical/dynamical model developed to forecast the post‐monsoon cyclone activities over the Bay of Bengal, where 80% of the TCs of the North Indian Ocean are originated. In the hybrid model, the coupled model CFSv2 predicts the large‐scale climate indices, and the principal component regression (PCR) model is used to relate these indices with the TC frequency. A solid concurrent relation between the cyclonic disturbance frequencies and various large‐scale variables is noted. The dynamical variable, for example, the zonal wind, acts as a precursor variable. We identified three concurrent predictors (ocean heat content over the Bay of Bengal, sea surface temperature (SST) over the Indian Ocean, and SST over the tropical central Pacific regions) and two precursor predictors (low‐level wind at equatorial Indian ocean and strength of upper‐level easterly jet over African coast) influencing the cyclonic disturbance frequencies over the Bay of Bengal. The concurrent predictors are calculated from the CFSv2 hindcast/forecast output and the precursor predictors are calculated from the reanalysis data. The predictors influencing the cyclonic disturbance over the Bay of Bengal are also influencing the cyclonic storms. Hence, the same predictors are used for developing a hybrid model for cyclonic disturbance and storm frequencies. A significant inter‐correlation among different predictors is observed and the PCR model avoids these inter‐correlations and, in this method, PCs are estimated on the predictors to make them orthogonal to each other. The hybrid model achieved a significant skill for seasonal cyclone forecast over the Bay of Bengal. Results suggest the potential for using the hybrid model for the operational seasonal forecasting of post‐monsoon cyclone activity over the Bay of Bengal.

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Prevalence of Sleep Practices, Circadian Types and Their Effect on Sleep Beliefs in General Population: Knowledge and Beliefs About Sleep and Sleep Practices (KNOBS Survey) - Divya Devaraj; Uma Devaraj; Kavitha Venkatnarayan; Chitra Veluthat; Priya Ramachandran; George D’Souza; K. Uma Maheswari (Sleep and Vigilance, 2021)

Beneficial microbiomes for bioremediation of diverse contaminated environments for environmental sustainability: present status and future challenges - Divjot Kour; Tanvir Kaur; Rubee Devi; Ashok Yadav; Manali Singh; Divya Joshi; Jyoti Singh; Deep Chandra Suyal; Ajay Kumar; Vishnu D. Rajput; Ajar Nath Yadav; Karan Singh; et al. (Environmental Science and Pollution Research, 2021)

Occurrence and removal of antibiotics from industrial wastewater - D. Akhil; Divya Lakshmi; P. Senthil Kumar; Dai-Viet N. Vo; A. Kartik (Environmental Chemistry Letters, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Purification and biochemical characterization of a novel secretory dipeptidyl peptidase IV from porcine serum - Divya Kumar; Vivek K. Hamse; K. N. Neema; Priya Babu Shubha; D. M. Chetan; Nanjunda Swamy Shivananju (Molecular and Cellular Biochemistry, 2020)

Assessing differential vulnerability of communities in the agrarian context in two districts of Maharashtra, India - Bhavana Rao Kuchimanchi; Divya Nazareth; Ramkumar Bendapudi; Suchita Awasthi; Marcella D’Souza (Climate and Development, 2019)

Psyhcrotolerant Bio-inoculants and Their Co-inoculation to Improve Cicer arietinum Growth and Soil Nutrient Status for Sustainable Mountain Agriculture - Nitin Rawat; Mansi Sharma; Deep Chandra Suyal; D. K. Singh; Divya Joshi; Pranjali Singh; Reeta Goel (Journal of Soil Science and Plant Nutrition, 2019)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Map-based cloning and validation of a gall midge resistance gene, Gm8, encoding a proline-rich protein in the rice variety Aganni - D. Divya; Nihar Sahu; Suresh Nair; J. S. Bentur (Molecular Biology Reports, 2018)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Development and Translational Application of an Integrated, Mechanistic Model of Antibody-Drug Conjugate Pharmacokinetics - Siddharth Sukumaran; Crystal Zhang; Douglas D. Leipold; Ola M. Saad; Keyang Xu; Kapil Gadkar; Divya Samineni; Bei Wang; Marija Milojic-Blair; Montserrat Carrasco-Triguero; Bonnee Rubinfeld; Paul Fielder; et al. (The AAPS Journal, 2017)

Effects of zolpidem alone and in combination with nabilone on cannabis withdrawal and a laboratory model of relapse in cannabis users - Evan S. Herrmann; Ziva D. Cooper; Gillinder Bedi; Divya Ramesh; Stephanie C. Reed; Sandra D. Comer; Richard W. Foltin; Margaret Haney (Psychopharmacology, 2016)

Divergent Perspectives on Landscape Connectivity Reveal Consistent Effects from Genes to Communities - Robert J. Fletcher; Noah S. Burrell; Brian E. Reichert; Divya Vasudev; James D. Austin (Current Landscape Ecology Reports, 2016)

Regulation of Gβγi-Dependent PLC-β3 Activity in Smooth Muscle: Inhibitory Phosphorylation of PLC-β3 by PKA and PKG and Stimulatory Phosphorylation of Gαi-GTPase-Activating Protein RGS2 by PKG - Ancy D. Nalli; Divya P. Kumar; Othman Al-Shboul; Sunila Mahavadi; John F. Kuemmerle; John R. Grider; Karnam S. Murthy (Cell Biochemistry and Biophysics, 2014)

Multiplicity of carbohydrate-binding sites in β-prism fold lectins: occurrence and possible evolutionary implications - Alok Sharma; Divya Chandran; Desh D. Singh; M. Vijayan (Journal of Biosciences, 2007)

Covalent enzyme immobilization onto glassy carbon matrix-implications in biosensor design - P. Sree Divya; D. Savitri; Chanchal K. Mitra (Journal of Biosciences, 1998)